DISKRESI KEPOLISIAN DALAM PENGHENTIAN PENYIDIKAN DI POLRESTA DENPASAR - Prasminda, Gede Dicka; Tangun Susila, I Wayan; Bela Siki Layang, I Wayan (Kertha Semaya : Journal Ilmu Hukum, 2013)
Police discretion is defined as the freedom of making decisions according to police discretion. Authority of police discretion in the termination of the investigation, it appears the authority under certain circumstances in the event or to make a decision whether or not the action will be carried out in the event of a crime. Discretionary powers held by police actually very broad because it is not set explicitly in the legislation. With the extent of that power, has the potential to be abused that power for their own advantage, groups, and other organizations. Though discretionary powers given if available legal channels to solve a problem is inefficient or inadequate.
Keywords: Discretion, Termination of Investigation